PENGARUH INDEKS SAHAM SYARIAH, VOLUME PERDAGANGAN DAN EARNING PER SHARE TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR: Studi Pada Bursa Efek Indonesia - Mohammad Irfani (Jurnal Studi Islam dan Sosial, 2019)
The Effect of Sharia Stock Index, Trade Volume and Earning Per Share on Stock Return in Manufacturing Company (Study on Indonesia Stock Exchange Year 2013-2015). The purpose of this study are: 1) To analyze the effect of sharia stock index on stock returns in manufacturing companies in 2013-2015. 2) To analyze the effect of trading volume on stock return in manufacturing company in 2013-2015. 3) To analyze the effect of Earning Per Share on stock return in manufacturing company in 2013-2015. The type of data used in this study is quantitative data and in the form of secondary data. The data is taken from the Indonesia Stock Exchange in the period 2013 to 2015. In this study will be observed is the Effect of Sharia Stock Index, Trading Volume and Earning Per Share Against Stock Return In Manufacturing Companies (Study on Indonesia Stock Exchange Year 2013-2015). This research uses quantitative research approach. Quantitative research is essentially emphasizing its analysis on numerical data (numbers) processed by statistical methods. The result of this research are: 1) From the result of hypothesis test of Syariah Sharia Index variable obtained tStatistic value equal to 1.438075 and Probability value equal to 0,0155 <0,05. So Sharia Stock Index has a positive and significant effect on Stock Return on manufacturing companies in Indonesia Stock Exchange period 2013-2015 period. 2) From the result of hypothesis test of Trade Volume variables obtained t-Statistic value of -0.088148 and Probability value of 0.9301> 0,05. So Trade Volume has negative and insignificant effect to Return of Stock at manufacturing company in Indonesia Stock Exchange period 2013-2015 period. 3) From result of hypothesis test of variable of Earning Per Share (EPS) obtained by t-Statistic value equal to 0,285553 and Probability value equal to 0,0377 <0,05. So Earning Per Share (EPS) has a positive and significant effect on Stock Return on manufacturing companies in Indonesia Stock Exchange period 2013-2015 period.